2021
DOI: 10.3389/fmicb.2021.703041
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Co-receptor Tropism Testing in HIV-1 Epidemic Region of Tanzania Where Multiple Non-B Subtypes Co-circulate

Abstract: HIV human immunodeficiency virus type I (HIV-1) entry inhibitor potency is dependent on viral co-receptor tropisms and thereby tropism determination is clinically important. However, phenotypic tropisms of HIV-1 non-B subtypes have been poorly investigated and the genotypic prediction algorithms remain insufficiently validated. To clarify this issue, we recruited 52 treatment-naïve, HIV-1-infected patients in Tanzania, where multiple HIV-1 non-B subtypes co-circulate. Sequence analysis of 93 infectious envelop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(65 reference statements)
0
4
0
Order By: Relevance
“…To assess the NAb titers of antisera, we employed a lentiviral reporter assay system pseudotyped by SARS-CoV-2 spike protein, as previously reported [ 19 ]. A version of spike protein which had been modified by truncating 19 amino acids from the C terminal end (CΔ19 spike) was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the NAb titers of antisera, we employed a lentiviral reporter assay system pseudotyped by SARS-CoV-2 spike protein, as previously reported [ 19 ]. A version of spike protein which had been modified by truncating 19 amino acids from the C terminal end (CΔ19 spike) was used.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, spike-encoding plasmids (kindly provided by T. Kuwata [ 18 ]) were modified by truncating the last 19 amino acids from the C-terminal end of the cytoplasmic tail to create plasmids designated as SARS-CoV-2 or VOC-Spike CΔ19. The lentiviral backbone, pSG3 ΔENVΔNef -Luc2-IN/HiBit (kindly provided by K. Tokunaga), was previously modified by inserting a HiBiT peptide tag sequence and a luciferase reporter gene [ 19 ]. The 2 modified plasmids were then used to co-transfect overnight-seeded 293T cells at a concentration of 1000 ng and 25 ng for pSG3 ΔENVΔNef -Luc2-IN/HiBit and SARS-CoV-2/VOC-Spike CΔ19, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this requires more phenotypic validation results to support this idea. Judicate's study demonstrated the limitation of currently available genotypic algorithms for predicting coreceptor inference among non-B subtypes (44). Therefore, the phenotypic tropism dataset of non-B subtypes is valuable for SGA to detect the HIV-1 variant populations with different coreceptor usages.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypic algorithms, including Geno2Pheno, WebPSSM, PhenoSeq, SCOTH, CoRSeqV3-C, and THETA, were developed to predict coreceptor use of clade B and non-B HIV-1 subtypes ( 39 , 58 ). However, these approaches may either underestimate or overestimate X4 tropism, depending upon the particular assay and the context in which it was used ( 59 61 ).…”
Section: Discussionmentioning
confidence: 99%